Akses Digital Marketing, HR Analysis and Financial Analysis Bootmaker Mr. Kye Shoes di Masa Pandemi COVID-19 - Utarsih, Henny; Susanti, Sussy (Universitas Ekuitas Indonesia, 2023)
Mr. Kye Shoes is a family-run company that few a is completing shoe orders for a number of organizations, including the TNI and an outsourcing firm for security guards. However, there is inadequate equipment, including shoe molding, to accommodate the large number of orders. Digital marketing is done by Mr. Kye Shoes, but only Shopee and the Facebook Marketplace are used for digital marketing. The company is prone to blending commercial operations with personal matters, and the COVID-19 pandemic caused a 50% drop in production activity. The community service program carried out by the team is to take a field work approach used to carry out tasks, and job descriptions, HR job descriptions, operational analysis, opportunity analysis, market and competition analysis, financial analysis, SWOT analysis, and digital marketing are all included in the company planning process. Keywords: Digital marketing, HR analysis, simple financial analysis, SWOT analysis, . Abstrak Mr. Kye Shoes adalah perusahaan keluarga yang menyelesaikan pesanan sepatu untuk sejumlah organisasi, termasuk TNI dan perusahaan outsourcing untuk satpam. Namun, peralatan yang ada belum memadai, termasuk moulding sepatu, untuk menampung pesanan dalam jumlah besar. Digital marketing dilakukan oleh Mr. Kye Shoes, namun hanya Shopee dan Facebook Marketplace yang digunakan untuk digital marketing. Perusahaan cenderung mencampurkan operasi komersial dengan urusan pribadi, dan pandemi COVID-19 menyebabkan penurunan aktivitas produksi sebesar 50%. Adapun Program pengabdian kepada masyarakat yang dilakukan tim, adalah dengan melakukan pendekatan kerja lapangan digunakan untuk melaksanakan tugas, dan uraian tugas, uraian tugas SDM, analisis operasional, analisis peluang, pasar dan saingan, analisis keuangan, analisis SWOT, dan pemasaran digital semuanya termasuk dalam proses pembuatan rencana perusahaan. Kata kunci: Digital marketing, analisis SDM, analisis keuangan sederhana, analisis SWOT.